Pengembangan Sistem Informasi Absensi Karyawan untuk Meningkatkan Efisiensi Manajemen Sumber Daya Manusia - Raihannunisak (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2021)
This study aims to develop and implement an Employee Attendance Information System to enhance the efficiency of human resource management within organizations. The system is designed to automate the tracking and recording of employee attendance, thereby reducing the reliance on manual processes and minimizing errors. Key features of the system include real-time attendance tracking, automated leave management, and detailed reporting capabilities. By utilizing biometric authentication and integration with existing HR systems, the attendance system ensures accuracy and reliability. The research discusses the design and development phases, including technology selection, system architecture, and user interface considerations. The system is evaluated based on its impact on operational efficiency, data accuracy, and user satisfaction. The results indicate that the implementation of the Employee Attendance Information System leads to significant improvements in attendance tracking, leave management, and overall HR operations. The paper also addresses the challenges encountered during the development and deployment of the system, along with the solutions implemented to ensure successful integration and user adoption.